Metal-Organic Frameworks Promoted Hydrogen Storage Properties of Magnesium Hydride for In-Situ Resource Utilization (ISRU) on Mars - Zhang, Ze; Wang, Yuanding; Wang, Haoming; Xue, Xiang; Lin, Qingguo (Frontiers in Materials, 2021)
Hydrogen is regarded as a promising solution to fulfill the energy demand of Mars human base in the future. Through in-situ resource utilization (ISRU) on Mars, the composite of metal-organic frameworks (MOFs) and magnesium hydride which demonstrates synergistic effect of physi- and chemisorption has been proposed to be an attractive approach for long-term hydrogen storage. MOFs may act either as scaffolds to confine Mg nanoparticles or as catalysts/precursors to lower the energy barrier for hydrogen dissociation on Mg surfaces. The corresponding mechanisms for faster hydrogenation/dehydrogenation kinetics and lower operation temperature were further discussed and analyzed.